2016
DOI: 10.1080/09205063.2015.1125564
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterizations,in vitroandin vivoevaluation of Etoricoxib-loaded Poly (Caprolactone) microparticles – a potential Intra-articular drug delivery system for the treatment of Osteoarthritis

Abstract: Intra-articular Drug delivery systems (IA-DDS) deliver the drug directly to the diseased joint space with significantly lowered systemic toxicities. In this work, we explored Etoricoxib (COX-2 inhibitor)-loaded Poly caprolactone (PCL) microparticles (MPs) as a potential IA-DDS. MPs were prepared by Oil/Water (O/W) emulsion-solvent evaporation method. Formulation parameters like polymer to drug ratio, stabilizer concentration were optimized to get the maximum encapsulation efficiency. The prepared particles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Additionally, the characteristic peaks of DOX and IR780 did not present in the XRD spectrum of mPEG-PAAV micelles/IR780+DOX as shown in Figure S7 , indicating that DOX and IR780 were successfully encapsulated in mPEG-PAAV micelles in their amorphous form. Previous studies have demonstrated that when drugs are encapsulated into the particle in their amorphous form, they lose their crystallinity 29 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the characteristic peaks of DOX and IR780 did not present in the XRD spectrum of mPEG-PAAV micelles/IR780+DOX as shown in Figure S7 , indicating that DOX and IR780 were successfully encapsulated in mPEG-PAAV micelles in their amorphous form. Previous studies have demonstrated that when drugs are encapsulated into the particle in their amorphous form, they lose their crystallinity 29 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…The use of larger particles that could better avoid lymphatic drainage and cell‐mediated particles elimination (Figure 1) is a potential strategy to achieve IA drug sustained release over longer periods of time. In fact, polycaprolactone (PCL) microparticles with an average size of 16 μm were found to remain in the joint space of rats for up to a month 79 . Janssen et al synthesized celecoxib‐loaded polyester amide (PEA) microspheres with a mean particle size of 25 μm and were able to detect around 20% of the injected PEA 12 weeks after IA injection in Lewis rats 80 .…”
Section: Intra‐articular Drug Delivery Strategies In Oamentioning
confidence: 99%
“…investigated the potential of polycaprolactone (PCL) microparticles to deliver drugs for OA (Arunkumar et al. 2016b). As in vivo results showed, the drug was slowly released, and the whole microparticles were still detected in the joint after one month.…”
Section: Drug Delivery Systems For Oa Therapymentioning
confidence: 99%